A multicenter, open‐label, phase II study of tirabrutinib (ONO/GS‐4059) in patients with Waldenström's macroglobulinemia. Issue 9 (20th July 2020) - Sekiguchi, Naohiro; Rai, Shinya; Munakata, Wataru; Suzuki, Kenshi; Handa, Hiroshi; Shibayama, Hirohiko; Endo, Tomoyuki; Terui, Yasuhito; Iwaki, Noriko; Fukuhara, Noriko; Tatetsu, Hiro; Iida, Shinsuke; et al.
Abstract: Tirabrutinib is a second‐generation Bruton's tyrosine kinase inhibitor with greater selectivity than ibrutinib. Here, we conducted a multicenter, phase II study of tirabrutinib in patients with treatment‐naïve (Cohort A) or with relapsed/refractory (Cohort B) Waldenström's macroglobulinemia (WM). Patients were treated with tirabrutinib 480 mg once daily. The primary endpoint was major response rate (MRR; ≥ partial response). Secondary endpoints included overall response rate (ORR; ≥ minor response), time to major response (TTMR), progression‐free survival (PFS), overall survival (OS), and safety. In total, 27 patients (18 in Cohort A; 9 in Cohort B) were enrolled. The median age was 71 y, and the median serum immunoglobulin M level was 3600 mg/dL. Among the patients, 96.2% had the MYD88 L265P mutation. MRR and ORR were 88.9% and 96.3%, respectively (Cohort A: MRR, 88.9%; ORR, 94.4%; Cohort B: MRR, 88.9%; ORR, 100%). Median TTMR was 1.87 mo. PFS and OS were not reached with a median follow‐up of 6.5 and 8.3 mo for Cohorts A and B, respectively. The most common adverse events (AEs) were rash (44.4%), neutropenia (25.9%), and leukopenia (22.2%), with most AEs classified as grade 1 or 2. Grade ≥ 3 AEs included neutropenia (11.1%), lymphopenia (11.1%), and leukopenia (7.4%). No grade 5 AEs were noted. All bleeding events were grade 1; none were associated with drug‐related atrial fibrillation or hypertension. Although the follow‐up duration was relatively short, the study met the primary endpoint. Therefore, tirabrutinib monotherapy is considered to be highly effective for both untreated and relapsed/refractory WM with a manageable safety profile. (JapicCTI‐173646). Abstract : We conducted a multicenter, phase II study of tirabrutinib in patients with treatment‐naïve or with relapsed/refractory Waldenström's macroglobulinemia. Although the follow‐up duration was relatively short, the study met the primary endpoint. Tirabrutinib monotherapy is considered to be highly effective for both untreated and relapsed/refractory WM with a manageable safety profile.